Analisis Pengaruh Strategi Promosi dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Restoran Domino’s Pizza Cabang Jababeka Bekasi (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2021)
The author conducted research at Domino’s Pizza Branch Jababeka Bekasi Branch, which is a fast food restaurant engaged in the food trade. This research was conducted to analyze how much influence the promotion strategy and service quality on purchasing decisions at the Domino’s Pizza Branch Jababeka Bekasi Branch. Data obtained through a questionnaire filled by consumers Domino’s Pizza as respondents as many as 80 people. The author uses the method of quantitative analysis and descriptive analysis. Quantitative analysis using SPSS statistics consisting of validity and reliability test, classic assumption test consisting of multicollinearity test, normality test, heteroscedasticity test and autocorrelation test, multiple linear regression analysis, goognes of fit test consisting of test coefficient of determination (R²), t test and test f. The calculation results from multiple linear regression coefficient analysis of the effect of promotion strategy and service quality on purchasing decisions are Y = -3.259 + 0.631X1 + 0.450X2 which indicates that if the promotion strategy and service quality are increased by one (X1 = 1 and X2 = 1) it will increase purchasing decisions by 0.631 and 0.450. Based on the calculation of the Determination Coefficient (R²) obtained a value of 0.573 or 57% which indicates the existence of a contribution between the promotion strategy and the quality of service to purchasing decisions. Based on the results of the spss data for the t test between the promotion strategy of the purchasing decision, getting the t count of 7.625 and the service quality of the purchasing decision obtained a value of t count of 5.293 greater than the t table value of 1.668, while the significance value was 0.00 (sig <0.05), it can be concluded that Ho is rejected and Ha is accepted. This shows a significant influence between promotion strategies and service quality on purchasing decisions. Based on the results of the spss data for the f test, the calculated value of 51.632 is greater than the value of 3.12, while the significance value obtained is 0.00 (sig <0.05), it can be concluded that there are positive and significant influences between promotion strategy variable (X1) and service quality (X2) together towards purchasing decisions (Y).